2018
DOI: 10.1002/lary.27392
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic Therapies in Ménière Disease: Evaluation of Outcomes and Early Vertigo Control

Abstract: Objective To evaluate outcomes of intratympanic (IT) dexamethasone and gentamicin in Ménière Disease (MD). Methods Charts of adult patients with unilateral definite MD receiving IT gentamicin or dexamethasone from 2005 to 2017 were retrospectively reviewed. All patients had at least 6 months follow‐up. Failure in each group was defined as the need for more aggressive therapy. Prior to 2011, all patient received IT gentamicin, administered as primary therapy after failure of conservative treatment measures. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Although not reaching statistical significance, there was a trend for a higher frequency of repeat injections required in the methylprednisolone than in the gentamicin group as perhaps expected, and recently reported in a retrospective series (n=33) using dexamethasone. 13 We acknowledge that there are several limitations with this follow-up study, including the absence of a placebo arm. It was felt that it would have been unethical to leave patients in the severely symptomatic stage of Menière's Disease untreated for up to 2 years, particularly in view of the 2014 gentamicin Vs placebo RCT which was stopped early and the 2011 Cochrane review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although not reaching statistical significance, there was a trend for a higher frequency of repeat injections required in the methylprednisolone than in the gentamicin group as perhaps expected, and recently reported in a retrospective series (n=33) using dexamethasone. 13 We acknowledge that there are several limitations with this follow-up study, including the absence of a placebo arm. It was felt that it would have been unethical to leave patients in the severely symptomatic stage of Menière's Disease untreated for up to 2 years, particularly in view of the 2014 gentamicin Vs placebo RCT which was stopped early and the 2011 Cochrane review.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] Dose-dependent hearing loss has been discussed, however, in recent studies with IT gentamicin, which have revealed that hearing outcomes can be comparable to IT steroids. 13,14 A literature review of ITS for Menière's disease was undertaken by one of our co-authors in 2017. 30 12 studies (6 prospective) meeting AAOHNS reporting guidelines were identified, of which 8 have been published since the 2011 ITS Cochrane paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though gentamicin as an antibiotic reduces vertigo in patients, it might also damage their vestibular function and worsen their hearing ( 10 ). Therefore, this drug is usually used for patients with MD who fail to receive conservative treatment ( 11 ). Dexamethasone is a synthetic corticosteroid with anti-inflammatory, anti-allergic, and immunosuppressive effects ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…First-line treatment includes dietary restrictions for salt, caffeine, and alcohol associated to drugs both for acute attacks (dimenhydrinate, benzodiazepines) 12 , and as prophylactic therapy (betahistine, β-blockers, diuretics) 13 . When first-line treatment does not offer satisfactory symptom control, intratympanic (IT) administration of gentamicin or corticosteroids can be performed 14 ; however, many studies showed that IT gentamicin may expose the patients to a risk of hearing loss, depending on dosage and intervals between administrations 15 . Labyrinthectomy or other surgical procedures can be suggested for intractable MD 16 .…”
Section: Introductionmentioning
confidence: 99%